Expectations of families of patients and the attitudes of medical staff — an analysis of the example of the Paediatric Hospital in Bielsko-Biala - Waksmańska, Wioletta; Łukasik, Renata; Gawlik, Katarzyna; Makowska-Songin, Julia (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. The topic of this paper is the analysis of interpersonal communication as well as mutual relations between parents of a hospitalized child and the hospital stuff taking care of her/him. Aim of the study. The major aim of the paper was to analyze the expectations of the parents of children at the paediatric ward towards the hospital stuff. Moreover, the paper aims at determining what kind of attitudes of the stuff facilitate correct communication with parents and simultaneously have positive impact on the child as a patient. Material and methods. The research was conducted during one month in the year 2010 in the Paediatric Hospital in Bielsko-Biała. It consisted in the analysis of two-part questionnaires filled in by 81 parents of children staying in the hospital. Results and conclusions. On the basis on conducted analysis it can be stated that most of the informants were satisfied with the cooperation with the hospital stuff and received a warm welcome. Among the most desired characteristics of the stuff one can mention kindliness, patience, politeness, good verbal communication, specialist knowledge and determination in action. In questions concerning attitudes hindering cooperation one can mention such features as indifference, haste, lack of interest, discourtesy and malice. However these characteristics were not common.